2011
DOI: 10.1108/14630011111136803
|View full text |Cite
|
Sign up to set email alerts
|

User preferences of office occupiers: investigating the differences

Abstract: PurposeThe work environment has been identified to influence employee satisfaction and work performance. In order to develop and provide work environments that meet the preferences of as many employees as possible, more information about user preferences and possible preference differences between different kinds of users is required. The purpose of this paper is to increase the understanding concerning office users' work environment preferences. The aim is to investigate whether there are differences in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…The perceived importance of specific needs might further clarify the effects of the workspace, personal characteristics and activities on their work environment satisfaction. For example, Rothe et al (2011) found significant effects of several personal characteristics on their preferences for the work environment. It is therefore assumed that the effects of personal characteristics on work environment satisfaction are at least partly mediated by the importance of employee needs.…”
Section: Indirect Effects Through Employee Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…The perceived importance of specific needs might further clarify the effects of the workspace, personal characteristics and activities on their work environment satisfaction. For example, Rothe et al (2011) found significant effects of several personal characteristics on their preferences for the work environment. It is therefore assumed that the effects of personal characteristics on work environment satisfaction are at least partly mediated by the importance of employee needs.…”
Section: Indirect Effects Through Employee Needsmentioning
confidence: 99%
“…External mobility, gender, age -Besides activity patterns, Rothe et al (2011) used three main characteristics to explore differences in preferences, namely external mobility (number of hours outside the office) and the personal characteristics age and gender. External mobility was operationalized as the time spent away from the office during working hours.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, the CRE manager has to identify the needs and preferences of office workers (Rothe et al 2011;Joy and Haynes 2011;Haynes 2011). To really understand office occupiers' needs the CRE manager has to establish not only the work process requirements, as previously described, but also the psychological needs of office occupiers (Oseland 2009).…”
Section: Processesmentioning
confidence: 99%
“…Many studies have proven the correlation between better work environment and user satisfaction (Rothe et al, 2011a, Leifer, 1998, Wilkinson et al, 2011, Ornetzeder et al, 2016. At the same time, we all know we need to save energy and renovation of existing buildings is a potential solution to reduce energy consumption.…”
Section: Introductionmentioning
confidence: 99%